Propojování počítačových aplikací - Bílková, Renáta (Univerzita Pardubice, 2006)
The number of enterprice applications used by companies is increasing rapidly. Needs of connection of all these systems and applications together and communication between enterprices (so-called bussiness to bussiness communication) and communication with public administration is currently increasing as well. This paper describes new trends in development of enterprise infromation systems and new facilities of application integration with emphasis on the web services.
Keywords: počítačové aplikace; Integrace; webové služby; jazyk XML; E-Government